Molecular mechanics applied to single-walled carbon nanotubes - Ávila,Antonio Ferreira (2008)
Single-walled carbon nanotubes, with stiffness of 1.0 TPa and strength of 60 GPa, are a natural choice for high strength materials. A problem, however, arises when experimental data are compiled. The large variability of experimental data leads to the development of numerical models denominated molecular mechanics, which is a "symbiotic" association of molecular dynamics and solid mechanics. This paper deals with molecular mechanics simulations of single-walled carbon nanotubes. To be able to evaluate the molecular mechanics model, the three major carbon nanotube configurations (armchair, zigzag and chiral) were simulated. It was proven that the carbon nanotube configuration has influence on stiffness. By varying the radius, hence the curvature, the Young's modulus changed from 0.95 TPa to 5.5 TPa, and the Poisson's ratio ranged from 0.15 to 0.29. The numerical simulations were in good agreement with those presented in the literature.